New and known species of Nothotylenchus Thorne, 1941 (Nematoda: Anguinidae) from Iran with an updated list of species - Hashemi, Kobra; Karegar, Akbar (Zootaxa, 2020)
During a survey conducted during 2013–2017, five known and two new species of Nothotylenchus Thorne, 1941 were collected from the southern provinces of Iran. N. brzeskii n. sp. is characterised by a body length of 774–922 µm, lateral fields with four incisures, delicate, short stylet (7–8 µm) with small rounded knobs, pyriform, offset or slightly overlapping basal pharyngeal bulb, posterior vulva position (V = 83.4–84.4), short PUS (5–10 µm), spicules 20.5–23 µm long, and thick tail with rounded to dull terminus. N. siddiqi n. sp. is characterised by a body length of 573–645 µm, six to nine incisures in lateral fields, delicate, short stylet (6.5–7.5 µm) with rounded knobs, pyriform or slightly elongate and offset basal pharyngeal bulb, V = 79.3–81.0, PUS = 26.5–40 µm, short spicules = 14.5–16.5 µm, and tail with rounded terminus. Morphometric data of the studied species are presented and intraspecific variation of their morphometrics and morphological characters is discussed. The list of world Nothotylenchus species is updated, and a dichotomous identification key and an updated tabular compendium for 41 valid species are provided.